Crop filling: A pipeline for repairing memory clinic MRI corrupted by partial brain coverage - Gonzalo Castro Leal; Tim Whitfield; Janaki Praharaju; Zuzana Walker; Neil P. Oxtoby (MethodsX, 2024)
Data-driven solutions offer great promise for improving healthcare. However, standard clinical neuroimaging data is subject to real-world imaging artefacts that can render the data unusable for computational research and quantitative neuroradiology. T1 weighted structural MRI is used in dementia research to obtain volumetric measurements from cortical and subcortical brain regions. However, clinical radiologists often prioritise T2 weighted or FLAIR scans for visual assessment. As such, T1 weighted scans are often acquired but may not be a priority, resulting in artefacts such as partial brain coverage being systematically present in memory clinic data.Here we present “MRI Crop Filling”, a pipeline to replace the missing T1 data with synthetic data generated from the T2 scan, making real-world clinical T1 data usable for computational research including the latest AI innovations. Our method consists of the following steps: • Register scans: T2 and (cropped) T1. • Synthesise a new T1 using an open source deep learning tool. • Replace missing (cropped) T1 data in original T1 scan and super-resolve to improve image quality.